Transsphenoidal Surgery : Complication Avoidance and Management Techniques - Laws, Jr, Edward R.; Cohen-Gadol, Aaron A.; Schwartz, Theodore H.; Sheehan, Jason P. (Springer International Publishing : Imprint: Springer, 2017)
This work details contemporary clinical knowledge on the multidisciplinary management of pituitary and other sellar/parasellar tumors, with a focus on surgical techniques and a particular emphasis on complication avoidance and management. International experts provide guidance on natural history, radiologic and clinical aspects, surgical indications, and resection techniques.In addition, case presentations and clinical photographs help the reader reduce the risk of error and advance their own surgical skills. Readers also have access online to streaming videos of key procedures to help them provide the best possible outcomes for every patient. Transsphenoidal Surgery: Complication Avoidance and Management Techniques will be of great value to Neurosurgeons, Otolaryngologists, Endocrinologists, Radiation Oncologists, and residents and fellows in these specialties.
Keywords: Medicine.; Endocrinology.; Neurosurgery.; Surgical oncology.; elektronické knihy; electronic books